Meta Analysis: The Effect of Bullying on Adolescents on Mental Health and Depression - Nurussyifa Afiana Zaen; Riya Ulin Nuha; Nindita Arum Veibiani (Masters Program in Public Health, 2022)
Background: Bullying is an act of aggression that is intentional and repeated physically, psychologically, verbally, and cyber which can cause various health problems. Bullying is one of the causes of poor mental health conditions in adolescents whose impact can continue into adulthood. This study was aimed to assess the magnitude of the effect of bullying on mental health and depression based on the scores obtained from several previous similar studies. Subjects and Method: The design of this research study was a systematic review and meta-analysis. The primary articles used were obtained from online databases (PubMed, Google Scholar, ResearchGate, and Springer Link) published in 2012-2022. Population: teenagers. Intervention: bullying. Comparison: not experiencing bullying. Outcomes: mental health and depression. The keywords used in the primary article search were “Bullying” AND “Mental Health Problem” OR “Psychological Disorder” OR “Psychological Distress” AND “Depression” OR “Depressive Disorder” AND “Adolescent” OR “Teenager”. This study uses full-text articles with a cross-sectional design and contains an aOR (adjusted Odds Ratio) value. The selection of articles was carried out using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application. Results: There are 7 articles from Saudi Arabia, Taiwan, Italy, Morocco, Sweden, Australia, and Ethiopia on bullying and adolescent mental health, as well as 8 articles from Saudi Arabia, US, Italy, China, Brazil, Canada, Australia, and Malaysia on bullying and depression in adolescents. The results of the meta-analysis showed that bullying was statistically significant in increasing the occurrence of mental health disorders (aOR= 2.48; 95%CI= 1.64 to 3.74; p< 0.001) and depression (aOR= 2.74; 95%CI= 2.29 to 3.28; p< 0.0001) in teenagers. Conclusion: The experience of bullying can increase the risk of mental health disorders and depression in adolescents. Keywords: Bullying, mental health, depression, youth. Correspondence: Riya Ulin Nuha. Faculty of Health Science, Universitas ‘Aisyiyah Yogyakarta. Jl. Ring Road Barat 63 Mlangi Nogotirto Gamping, Sleman 55292, Yogyakarta, Indonesia. Email: ulin514@gmail.com. Mobile: 081238710748.